A mapping study on the feasibility of method engineering. Issue 12 (30th January 2014) - Kuhrmann, Marco; Méndez Fernández, Daniel; Tiessler, Michaela
ABSTRACT Software processes have become inherently complex to cope with the various situations we face in project environments. In response, the research area of method engineering arose in the 1990s aiming at the systematization of process construction and application. Although the research area has gained much attention and offered a plethora of contributions so far, we still have little knowledge about which basic concepts are finally established and what their feasibility is. To overcome this shortcoming, we need a systematic investigation of the publication flora in method engineering. To reach this aim, we contribute a systematic mapping study and investigate, inter alia, which contributions were published over time and which research type facet they address to distill a common understanding about available method engineering concepts and their maturity. On the basis of the review of 83 publications, our results show that even if a high number of contributions is available, most of those contributions only repeat and discuss formerly introduced concepts, whereas reports on empirically sound evidence on the feasibility are still missing. Although the research area constitutes a many contributions, yet missing are a common understanding of method engineering and empirically sound investigations that would allow for practical application and experience extraction. Copyright © 2014 John Wiley & Sons, Ltd.